Ethical attitudes of practicing librarians and LIS academics : is there a difference? - Horvat, Aleksandra knjižničarka (Array, 2010)
Professional ethics seems to be gaining importance as the library environment changes under the influence of new technologies and new legislation of concern for libraries is continuously introduced. The changing environment may create uneasiness among the library staff who might not always be sure how to react in new situations. Therefore librarians should learn about ethical issues and professional ethics has become a legitimate topic in both LIS curricula and professional training courses. It might seem that LIS educators will be the first to adopt the library ethics principles and live by them. But in fact they also belong to another professional community – the academic profession – which has its own values which may or may not correspond to the professional values of librarians. In the times when the library profession is confronted with numerous challenges and when voices are raised that it should reexamine its position in the society, it is extremely important that LIS educators and practicing librarians share the same professional ethics. In order to understand the professional values of the LIS academic staff, an investigation of their ethical attitudes will be carried out. The investigation will be based on a specially developed questionnaire and an accompanying interview if needed. The results will be commented and compared to the results obtained in two earlier investigations on the ethical attitudes of practicing librarians which were carried out in 2002 and 2006. The aim of the paper is to find out if the whole library community in Croatia share the same professional values.